Komposisi dan Kerapatan Jenis Alga di Taman Wisata Perairan Laut Banda di Kabupaten Maluku Tengah - Rombe, Katarina Hesty; Rahman, Abdul; Mardiana, Mardiana; Rosalina, Dwi (Politeknik Negeri Sambas, 2023)
The purpose of this study was to identify the type of algae, calculate the composition, density, diversity index, similarity index, and dominance index, and measure water quality parameters in the waters of the Banda Sea marine tourism park in central Maluku Regency. The method used in this study is a line transect method and a quadrant frame measuring 1m x 1m. There are 3 stations used with 5 replications each. The results showed that there were three divisions of algae, namely Chlorophyta, Phaeophyta, and Rhodophyta, with details of the species obtained were Amphiroa fragilissima, Boodlea composita, Boergesenia forbesii, Cladophora, Chaetomorpha crassa., Dictyota dichotoma, Gracilaria edulispuntia, Halimeda macrophyopuntia. tuna, Padina australis, Ulva compressa, Ulva reticullata, and Valonia ventricosa. The Chorophyta division of 66% obtained the highest species composition value, the highest density was obtained by the Amphiroa fragilissima species of 0.205. In addition, the ecological index such as (1) the diversity index was in the medium category with a value range of 1.35-1.97, (2) the similarity index was included in the high category with a value range of 0.72-0.86 which indicates that the ecosystem is in a stable condition and the dominance index of the three stations shows a value close to one, namely 0.87-1 which indicates that there is a tendency for one species to dominate. The measurements of water quality parameters such as temperature, salinity, and currents show that they are optimal for algae growth.